2002
DOI: 10.1126/science.1072838
|View full text |Cite
|
Sign up to set email alerts
|

Public Information and Breeding Habitat Selection in a Wild Bird Population

Abstract: According to the "public information" hypothesis, some animal species may monitor the current reproductive success of conspecifics to assess local habitat quality and to choose their own subsequent breeding site. To test this hypothesis experimentally, we manipulated two components of public information, the mean number of offspring raised locally ("quantity") and their condition ("quality"), in the collared flycatcher Ficedula albicollis. Immigration rate decreased with local offspring quantity but did not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
443
4
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 439 publications
(470 citation statements)
references
References 26 publications
19
443
4
4
Order By: Relevance
“…Secondly, nest building is very costly in terms of time and energy for white storks (Vergara et al 2010), so it could be more advantageous for newly recruited, inexperienced birds to occupy an old nest in the neighbourhood of a high-quality pair, instead of building a new one in a previously unoccupied area. Finally, it cannot be excluded that first-time breeders use reproductive success of more experienced conspecifics as a public information on the quality of habitat patches, which has been reported for a number of other avian species (Doligez et al 2002). Under such circumstances, young inexperienced storks could be attracted to settle close to the high-quality pairs which raise, on average, more fledglings than pairs of lower quality.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, nest building is very costly in terms of time and energy for white storks (Vergara et al 2010), so it could be more advantageous for newly recruited, inexperienced birds to occupy an old nest in the neighbourhood of a high-quality pair, instead of building a new one in a previously unoccupied area. Finally, it cannot be excluded that first-time breeders use reproductive success of more experienced conspecifics as a public information on the quality of habitat patches, which has been reported for a number of other avian species (Doligez et al 2002). Under such circumstances, young inexperienced storks could be attracted to settle close to the high-quality pairs which raise, on average, more fledglings than pairs of lower quality.…”
Section: Discussionmentioning
confidence: 99%
“…vegetation structure (Orians & Wittenberger 1991) or presence of parasites (Boulinier et al 2001)) that are linked to the reproductive success of conspecifics. A recent manipulation of the local reproductive performance of conspecifics in a population of collared flycatchers (Ficedula albicollis) showed that individual habitat selection is linked to public information (Doligez et al 2002). This study further hypothesized that individuals use different measures of public information for settlement and departure decisions because of individualspecific constraints on information gathering behaviour (Doligez et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In nature, however, individuals are likely to deviate from such ideal expectations because of (i) constraints acting on individual spatial knowledge and (ii) limited reliability of cues used in assessing habitat quality (Orians & Wittenberger 1991;Lima & Zollner 1996). Recent theoretical (Boulinier & Danchin 1997;Danchin et al 2001;Doligez et al 2003a) and experimental (Boulinier et al 2002;Doligez et al 2002) studies suggest that public information (i.e. information derived from the reproductive performance of conspecifics (Valone & Giraldeau 1993;), may be highly reliable information for selecting a breeding habitat, provided the environment is sufficiently predictable in time (Boulinier & Danchin 1997;Doligez et al 2003a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategies adopted by individuals to minimize this uncertainty rely on adaptive behaviour processes [7], in which animals use biological information (hereafter we will use the nomenclature and definitions proposed in [8]) to adjust their behaviour to the environmental and intrinsic factors related to reproductive success. Behavioural processes include dispersal versus philopatry (at either intra-or interpopulation level [9][10][11]), divorce versus mate retention [12,13], as well as habitat [14] and mate [15] selection.…”
Section: Introductionmentioning
confidence: 99%